1998
DOI: 10.1111/j.1600-0765.1998.tb02203.x
|View full text |Cite
|
Sign up to set email alerts
|

A study of the proliferative activity of the long junctional epithelium using argyrophilic nucleolar organizer region (AgNORs) staining

Abstract: The proliferative activity of the long junctional epithelium (LJE) in rats was examined using stains for argyrophilic proteins of the nucleolar organizer region (AgNORs protein). The LJE was experimentally produced by insertion of a rubber piece between maxillary molars for 1 wk. After removal of the rubber, the length and AgNORs parameters of the LJE were measured and analyzed statistically. The LJE widely covered the apical side of the exposed root surface 4 wk after the removal. Its length was longest after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
15
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 27 publications
1
15
0
Order By: Relevance
“…Several investigators have proposed that DAT cells may be nonmigratory cells and that they do not participate in the turnover of the junctional epithelium (3,14,15). In contrast, other studies have reported evidence supporting a high turnover of DAT cells (16)(17)(18)(19). Thus, questions remain about whether DAT cells migrate to participate in cell turnover of the junctional epithelium (regardless of their expression of adhesion proteins), why there is no laminin (other than laminin-5) expressed in the internal basal lamina and how adhesion proteins are related to turnover of the junctional epithelium.…”
mentioning
confidence: 99%
“…Several investigators have proposed that DAT cells may be nonmigratory cells and that they do not participate in the turnover of the junctional epithelium (3,14,15). In contrast, other studies have reported evidence supporting a high turnover of DAT cells (16)(17)(18)(19). Thus, questions remain about whether DAT cells migrate to participate in cell turnover of the junctional epithelium (regardless of their expression of adhesion proteins), why there is no laminin (other than laminin-5) expressed in the internal basal lamina and how adhesion proteins are related to turnover of the junctional epithelium.…”
mentioning
confidence: 99%
“…It is well known that the long junctional epithelium forms clinically on the exposed root surface following periodontal surgery such as root planning and curettage (3–7). Numerous studies have also demonstrated that the long junctional epithelium can be detected in animals with experimentally produced periodontitis (8–18).…”
mentioning
confidence: 99%
“…It has been reported that once produced on the root surface the long junctional epithelium is replaced with connective tissues during the course of wound healing in two different rat models, created by inserting a rubber piece between the molar teeth or by periodontal surgery (6, 14, 17, 18). Those studies have noted that the rat epithelial attachment with the long junctional epithelium is displaced coronally and that the apical portion of the long junctional epithelium is eventually replaced by connective tissue.…”
mentioning
confidence: 99%
“…A high‐level homology of the cell skeleton comprising the two tissues has been shown (4). Although Waldo’s method is not only used in the orthodontic field (32,33), but also in studies on periodontal disease (34,35), no study on the relationship between the epithelium and periodontal ligament epithelial cell clusters has been reported. While no continuity was present between the gingival epithelial rete pegs and periodontal ligament epithelial cell clusters in the control group and in the early stage, stratified gingival epithelium and elongated rete pegs were found close to large cell clusters on day 14.…”
Section: Discussionmentioning
confidence: 99%